Determinants of quality of life in survivors of cardiac arrest - Moulaert, VRMP; Wachelder, EM; Verbunt, JA; Wade, DT; van Heugten, CM (Journal of rehabilitation medicine, 2010)
To study factors related to quality of life after a hypoxic period due to cardiac arrest. Retrospective cohort study. Eighty-eight survivors of out-of-hospital cardiac arrest, admitted to a Dutch academic hospital between 2001 and 2006. Patients received a set of questionnaires at home. The main outcome measures were physical and mental quality of life (Medical Outcomes Study 36-item Short Form Health Survey; SF-36). Potential determinants were cognitive complaints, emotional problems depression/anxiety), post-traumatic stress, fatigue, daily functioning and participation in society. Multiple linear regression analyses were performed with physical and mental quality of life as dependent variables. Sixty-three (72%) patients responded. Mean time since cardiac arrest was 36 months (standard deviation (SD) 19). Backward regression analyses showed that physical quality of life was significantly (p < 0.001, adjusted R2 = 0.531) related to cognitive complaints (beta = -0.378), instrumental daily life activities (beta = 0.262), post-traumatic stress (beta = -0.246) and fatigue (beta = -0.226). Mental quality of life was significantly (p < 0.001, adjusted R2 = 0.664) explained by anxiety/depression (beta = -0.609), fatigue (beta = -0.177) and cognitive complaints (beta = -0.175). Quality of life is related to cognitive complaints, fatigue, anxiety/depression, post-traumatic stress and difficulties in daily activities in survivors of out-of-hospital cardiac arrest. Rehabilitation programmes for this group should specifically address these topics.